Molecular diagnosis of antimicrobial resistance in Escherichia coli. (4th March 2018) - Fleece, Molly E; Pholwat, Suporn; Mathers, Amy J; Houpt, Eric R
ABSTRACT: Introduction : Antimicrobial resistance is a growing global public health threat. The complexities of antimicrobial resistance in gram-negative bacteria such as Escherichia coli pose significant diagnostic and therapeutic challenges. Molecular diagnostics are emerging in this field. Areas covered : The authors review the clinical importance of pathogenic E. coli and discuss the mechanisms of resistance to common antibiotics used to treat these infections. We review the literature on antimicrobial susceptibility testing and discuss the current state of phenotypic as well as molecular methodologies. Clinical vignettes are presented to highlight how molecular diagnostics may be used for patient care. Expert commentary : The future use of molecular diagnostics for detection of antimicrobial resistance will be tailored to the context, whether hospital epidemiology, infection control, antibiotic stewardship, or clinical care. Further clinical research is needed to understand how to best apply molecular diagnostics to these settings.